The relationship between microstructure and fracture toughness of zirconia toughened alumina (ZTA) added with MgO and CeO2 - Rejab, Nik Akmar; Ahmad Azhar, Ahmad Zahirani; Ratnam, Mani Maran; Ahmad, Zainal Arifin (Elsevier, 2013)
The aim of this research is to investigate the mode of crack propagation in zirconia toughened alumina (ZTA) added with MgO and CeO2, respectively. The mode of crack refers to the toughening mechanism of the materials. Different ZTA compositions containing MgO and CeO2 as sintering additives were prepared using pressureless sintering at 1600 °C. Each sample was subjected to Vickers indentation with 294 N load and the cracks that propagated were observed with SEM. The ZTA with an addition of 0.7 wt.% MgO showed a crack deflection with a fracture toughness value of 6.19 ± 0.26 MPa · √m. On the other hand, the ZTA with CeO2 addition of 0.5 to 7 wt.% showed both crack bridging and deflection, and produced 5.78 ± 0.16 MPa · √m to 6.59 ± 0.23 MPa · √m fracture toughness values, respectively. The fracture toughness of the ZTA–MgO–CeO2 compositions is higher due to crack bridging and crack deflection. The toughening mechanisms of crack deflection and bridging hinder crack propagation since more energy is required to make the crack propagate. However, the formation of CeAl11O18 phase was observed; this consequently decreases the hardness and fracture toughness of the ZTA–MgO–CeO2 compositions.